2010
DOI: 10.1530/rep-09-0050
|View full text |Cite
|
Sign up to set email alerts
|

IGF1 induces up-regulation of steroidogenic and apoptotic regulatory genes via activation of phosphatidylinositol-dependent kinase/AKT in bovine granulosa cells

Abstract: IGF1, a potent stimulator of cellular proliferation, differentiation and development, regulates granulosa cell steroidogenesis and apoptosis during follicular development. Depending upon species and stage of follicular growth, IGF1 acts on granulosa cell steroidogenesis either alone or together with FSH. We examined the mechanism of action of IGF1 in bovine granulosa cells in serum-free culture without insulin to determine its potential role in the regulation of steroidogenic and apoptotic regulatory gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 68 publications
5
77
1
Order By: Relevance
“…Mechanism of PKA-enhanced IRS1 Y*MXM Phosphorylation by the IGF-1R-The well recognized synergy between FSH and IGF-1 at the level of gene expression (23,(31)(32)(33)(34)(35)(36)(37)(38) spearheaded our identification of the site of intersection between these two signaling pathways and, consequently, the mechanism by which FSH via PKA activates PI3K/AKT. Our results place IRS1 Y*MXM phosphorylation as a pivotal step in the activation of PI3K/AKT in GCs in response to FSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanism of PKA-enhanced IRS1 Y*MXM Phosphorylation by the IGF-1R-The well recognized synergy between FSH and IGF-1 at the level of gene expression (23,(31)(32)(33)(34)(35)(36)(37)(38) spearheaded our identification of the site of intersection between these two signaling pathways and, consequently, the mechanism by which FSH via PKA activates PI3K/AKT. Our results place IRS1 Y*MXM phosphorylation as a pivotal step in the activation of PI3K/AKT in GCs in response to FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous IGF-1 alone (in the absence of FSH) also activates PI3K/AKT in GCs (3) but does not promote gene expression (23,32,33). However, numerous studies have reported that exogenous IGF-1 potentiates gene expression responses to FSH (23,(31)(32)(33)(34)(35)(36)(37)(38). IGF-1 does not alter the affinity of FSH for its receptor (37), suggesting an intracellular intersection of the two hormonal pathways downstream of the FSH receptor.…”
mentioning
confidence: 99%
“…Therefore, to verify the involvement of the PI3K in the regulation of ovine primordial follicle activation in vitro, we tested the hypothesis that pharmacological inhibition of the PI3K pathway with LY294002 would inhibit the initiation of follicle growth. LY294002 has been used at different concentrations (from 1 ÎŒM to 50 ÎŒM) and incubation periods (from 20 min to 14 days) to inhibit the PI3K pathway in different ovarian cells (Reddy et al, 2009;Mani et al, 2010;Adhikari et al, 2013;Zhang et al, 2014;Fujihara et al, 2014;Lan et al, 2017). In this study, although the concentration of the inhibitor (50 ”M LY294002) is higher than most of the other studies (Keating et al, 2009;Sobinoff et al, 2012;Zhang et al, 2014;Zhao et al, 2017), our findings support the idea that this concentration was not toxic because it did not reduce the percentage of normal follicles compared to the treatment without the inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…51 embryo development and is affected by the pubertal status of the female (Pawlak et al, 2015) and FSH levels, which maintain the expression of BAX and BCL2 genes in the granulosa cells (Mani et al, 2010).…”
Section: Effects Of Pi3k and Fsh On Steroidogenesis Viability And Emmentioning
confidence: 99%